2019
DOI: 10.1097/md.0000000000017533
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of laparoscopic repeat liver resection for recurrent liver cancer

Abstract: Background:With the improvements of surgical instruments and surgeons’ experience, laparoscopic liver resection has been applied for recurrent tumors. However, the value of laparoscopic repeat liver resection (LRLR) is still controversial nowadays, which compelled us to conduct this meta-analysis to provide a comprehensive evidence about the efficacy of LRLR for recurrent liver cancer.Methods:A computerized search was performed to identify all eligible trials published up to April 2019. This meta-analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, the high postoperative recurrence rate and residual stone rate of intrahepatic bile duct stones, and there is no effective method to prevent postoperative recurrence, making hepatolithiasis become a refractory disease in biliary surgery.Research shows that after surgical treatment of patients with hepatolith 8 years, the recurrence rate is as high as 30.9% [10], which means that most patients often require again even surgical treatment for many times. But,the history of intra-abdominal surgery has been considered a relative contraindication for laparoscopic surgery during the early years of use [11].Although previous studies had shown that laparoscopic repetitive liver resection is safe and feasible in patients with a history of upper abdominal surgery or even a history of hepatectomy, these studies rarely involve the disease of IHD [12][13][14].Patients with IHD usually have perihepatic adhesions, anatomic distortion of the hilar area and intrahepatic biliary structure, and brotic parenchyma,biliary cirrhosis and portal hypertension that may increase the operative di culty and risk of complications.This requires the operator to be highly skilled in laparoscopy and surgery.Therefore, for the choice of surgical methods for patients with recurrent hepatolithiasis, the vast majority of doctors still choose the more conservative traditional open surgery.The opposite is that Most patients have great fear of traditional surgery and often refuse to have another operation, which leads to deterioration of the condition and seriously affects the physical and mental health of the patients [15,16].With the popularization of minimally invasive concept, more and more patients are eager to get minimally invasive treatment.Whether patients with recurrent intrahepatic bile duct stones can undergo laparoscopic hepatectomy has become an urgent question to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high postoperative recurrence rate and residual stone rate of intrahepatic bile duct stones, and there is no effective method to prevent postoperative recurrence, making hepatolithiasis become a refractory disease in biliary surgery.Research shows that after surgical treatment of patients with hepatolith 8 years, the recurrence rate is as high as 30.9% [10], which means that most patients often require again even surgical treatment for many times. But,the history of intra-abdominal surgery has been considered a relative contraindication for laparoscopic surgery during the early years of use [11].Although previous studies had shown that laparoscopic repetitive liver resection is safe and feasible in patients with a history of upper abdominal surgery or even a history of hepatectomy, these studies rarely involve the disease of IHD [12][13][14].Patients with IHD usually have perihepatic adhesions, anatomic distortion of the hilar area and intrahepatic biliary structure, and brotic parenchyma,biliary cirrhosis and portal hypertension that may increase the operative di culty and risk of complications.This requires the operator to be highly skilled in laparoscopy and surgery.Therefore, for the choice of surgical methods for patients with recurrent hepatolithiasis, the vast majority of doctors still choose the more conservative traditional open surgery.The opposite is that Most patients have great fear of traditional surgery and often refuse to have another operation, which leads to deterioration of the condition and seriously affects the physical and mental health of the patients [15,16].With the popularization of minimally invasive concept, more and more patients are eager to get minimally invasive treatment.Whether patients with recurrent intrahepatic bile duct stones can undergo laparoscopic hepatectomy has become an urgent question to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…Besides our study, the studies include patients with other diseases than HCC with few data for long-term results. However, adding of only a few existing metaanalyses [34,35] , they all mentioned that LRLR for selected patients is feasible with, at least, comparable results to open procedure.…”
Section: The Propensity Score Matching Study For Hcc Patientsmentioning
confidence: 99%
“…In addition, radiofrequency ablation (RFA), a minimally invasive option, has emerged as another alternative treatment modality for early‐stage HCC 9,10 . Several studies have previously recommended RHR when possible in the treatment of recurrent HCC 11–13 . However, conflicting data have shown that RFA, with relatively few complications, could achieve survival outcomes comparable to those of RHR for recurrent early‐stage HCC 14–16 .…”
Section: Introductionmentioning
confidence: 99%